CLIL and non-CLIL students’ beliefs about language - Sylvén, Liss Kerstin (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2015)
This article presents the findings of an innovative qualitative study involving one CLIL (content and language integrated learning) student and one student in a parallel, non-CLIL strand at high school level in Sweden. The aim of the study was to investigate differences in students’ beliefs about language. The success of second (L2) and foreign language (FL) learning depends to a large degree on individual differences (Dörnyei, 2005; Skehan, 1991). Differences are normally elicited through questionnaires, interviews, and/or observations. In the present study, the aim was to get direct access to the informants’ own perspectives, without the content being too directed through predetermined questions. In this study, students were asked to take photos illustrating how they view (a) their L1 (Swedish), and (b) the FL/L2 English. Then the photos were thematically organized by the researcher. Subsequently, the thematic organization and the photos themselves were discussed with each of the informants during an interview. The informants were asked to elaborate on each theme and/or picture as to why and how it illustrates the respective language for them. The findings reveal substantial differences between the two informants in their views on their L1 and FL/L2, with the CLIL student highlighting communication rather than seeing the two languages as separate systems, and the non-CLIL student seeing language rather the other way around.
Keywords: individual differences; learner beliefs; CLIL; visual narratives